TIJAUAN HUKUM ISLAM TERHADAP KONSEP PEMBAGIAN SAMA RATA HARTA WARIS (Studi Kasus Kampung Cipari Desa Sukarasa Kecamatan Pangatikan Kabupaten Garut ) - Fauzan Al-As’ari; Muhammad Muhammad (Kampus Akademik Publiser, 2024)
It cannot be denied that inheritance issues are a crucial aspect of human life. Inheritance arises from three main conditions. First, there is someone who dies, who is called the heir. Second, there is inheritance which consists of wealth owned by the heir. Third, there are individuals or groups who receive the inherited assets, who are called heirs. This inheritance process shows the transfer of rights in the form of property from the heir to the heirs.Inheritance law in Islam is an important and fundamental aspect, which is directly reflected in sacred texts whose existence has been agreed upon. Islamic inheritance law occupies a significant position in the series of Islamic law, becoming one of the pillars of the applicable law. The research approach in this context is normative-juridical, where law is conceptualized as what is written in statutory regulations (law in books) or as rules and norms that become the benchmark for human behavior.In the practice of dividing inheritance in several communities in Cipari Village, Sukarasa Village, Pangatikan District, Garut Regency, it is explained in article 183 that the heirs can agree to make peace in dividing the inheritance after each is aware of their share. Based on this statement, the distribution of inheritance equally is considered valid as long as each heir voluntarily shares it in a family or peaceful manner in accordance with the agreement of all parties involved. In practice, inheritance distribution is often carried out by deliberation to reach consensus and ensure that each party feels fair and satisfied with the results of the distribution. Thus, the inheritance process is not just a transfer of property rights, but also involves social and justice aspects that are important to maintain harmony in the family and society.